Efek Mediasi Motivasi Kerja Terhadap Kinerja Karyawan dengan Pengaruh Persepsi Budaya Organisasi dan Persepsi Kompensasi pada Karyawan BUMN PT X - Diah Putri Ningrum; Hardani Widhiastuti; Rusmalia Dewi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This research was conducted with the aim of analyzing the mediating effect of work motivation on employee performance with the influence of perceptions of organizational culture and perceptions of compensation on employees of BUMN PT X. The number of respondents to this research was 100 people. The research sample was taken using a saturated sampling technique. The research data was collected using scales for perceptions of organizational culture, perceptions of compensation and work motivation, while performance data used secondary data from the state-owned company PT X. Data analysis used the SEM program with SmartPLS. The research results show a positive and significant influence between perceptions of organizational culture on employee performance with a calculated t value of 2,517 > 1.96 and a p value of 0.012 < 0.05. Perception of Compensation has a positive and significant effect on Employee Performance with a t value of 3,846 > 1.96 and a p value of 0.000 < 0.05. Perception of Organizational Culture has a positive and significant effect on work motivation with a calculated t value of 6,608 > 1.96 with a p value of 0.000 < 0.05. Perception of Compensation has a positive and significant effect on work motivation with a calculated t value of 2,193 > 1.96 with a p value of 0.028 < 0.05. Work motivation has a positive effect on employee performance with a calculated t value of 4,806 > 1.96 with a p value of 0,000 > 0.05. The results of this research also conclude that there is a positive influence between perceptions of organizational culture on employee performance through work motivation with a calculated t value of 3,627 > 1.96 with a p value of 0.000 < 0.05. The positive influence of perceived compensation on employee performance through work motivation with a calculated t value of 2,195 > 1.96 with a p value of 0.028 < 0.05